ECONOMETRIC METHODS IN FORECAST EVALUATION OF THE DEVELOPMENT STRATEGY OF A MANUFACTURING SYSTEM - A. N. Mardas; O. A. Gulyaeva (Дискурс)
The article is devoted to the problem of predictive evaluation of the development strategy efficiency of a manufacturing system under non-stationary conditions. A toolkit for reducing the uncertainty of the future system state is presented proceeding from methods of nonparametric econometrics. The approach is based on the randomization methodology of empirical data and identification of the constructed distribution, as a model for the development after the bifurcation point. Identification is carried out using a nonparametric consent criterion. The really achievable indicators of the development strategy can be determined based on the constructed model.